Uso de fontes alternativas de potássio para a cultura do milho verde orgânico - Maciel, Robson Jardellys de Souza (2014)
The potassium (K) is a nutrient which is absorbed in the initial phase of plant development and its absortion influenced in corn productivity. Alternative sources of K may be responsible for high nutrient efficiency and reduce costs and minimizes the dependence of external inputs. This research aims to evaluate alternative sources of K and identify the nutrient use efficiency in nutrition and productivity. We setup na fied experiment in completely radomized blocks with four repetitionsand six treatments: wood ash (CZM), marble rock powder (PRM), potassium sulfate (SFP), organic compost, marble rock powder + wood ash (PRM+CZM), potassium sulfate + wood ash (SFP+CZ), potassium sulfate + marble rock powder (SFP+PRM). After 45 and 72 days after emergence (DAE) plants were sampled in each plot to quantify the dry biomass production, yield and nutrient use efficiency. In every plant fraction (leaf, stem, inflorescence and grains), the treatments with application of alternative sources of K affected the dry mass of plants and ear corn and also influenced the K-content and ear corn yield. The treatments affected the Kcontent in mayze plant. The nutrient use efficiency of K in the both sampling times were influenced by the alternative sources. It’s possible to adopt this alternative sources as substitution to the solubles potassium sulfate